FORMAÇÃO CONTINUADA DE PROFESSORES DA EDUCAÇÃO BÁSICA NO BRASIL E NA ARGENTINA: UM ESTUDO COMPARADO DE POLÍTICAS DE FORMAÇÃO EM CONTEXTO EDUCACIONAL INCLUSIVO - FERREIRA, PALOMA DOMINGUES (2020)
The research had as aim at a cross-cultural investigation to analyze policies for continuing education for teachers of Basic Education for educational context in Brazil and Argentina. Data were analyzed from the cross-cultural perspective according to Aguilar (2013) and Bereday (1972). The option for cross-cultural education allowed understand a foreign education system compared to the Brazilian one. Further, cross-cultural investigation allowed understand, verify, and interpret the discourses in policies for continuing training for Basic Education teachers in the inclusive context in the countries mentioned. Besides, the option was for hermeneutical method by Gadamer (1997), Ricouer (1988), Palmer (1997) and others. Therefore, hermeneutical is understood as a viable path to carry out the research, because it starts from documents and international guidelines (macro context) to Latin American countries to achieve a specific reality, in other words, continuing teacher training for inclusive context in Brazil and Argentina. Through data analysis was possible identify that both countries present a trend, within their particularities, regarding policies for continuing teacher training of Basic Education in educational inclusive context. Moreover, regarding the concept of inclusion adopted in Brazil, documents bring the matter of training to inclusive context considering especially disabled students and those with special educational needs (NEE in Portuguese acronym) inserted in regular common groups, whole in Argentina, the inclusion matter arises as an answer to inequalities. From these ways to express inclusion in each country, regarding teacher continuing training for Basic Education who work with students in regular common groups, legal apparatus makes restricted mentions, because when continuing teacher training is mentioned, the reference is to specialized teachers for working with Specialized Educational Service (AEE in Portuguese acronym), not to those who work with regular common classes in whose groups the students with NEE students inserted in. Brazil presents a larger range of documents and programs when compared to Argentina, but neither country has a document, excerpt within a document, or even a program that contemplates this group of teachers.